A novel solvent-free co-grinding preparation improves curcumin bioavailability in healthy volunteers: A single-center crossover study. Issue 1 (January 2023) - Wang, Chenjing; Jiang, Xin; Zhang, Xiaolei; Xu, Yi; Li, Li; Li, Xin; Wang, Shanglong; Shi, Ping; Gao, Xiaomeng; Liu, Zimin; Clark, W. Dennis; Cao, Yu
Abstract: Curcumin, from the rhizome of turmeric ( Curcuma longa L.), has a wide variety of biological activities. Unfortunately, its poor water-solubility greatly limits its bioavailability. The purpose of this study was to evaluate CUMINUP60®, a novel preparation utilizing a solvent-free, co-grinding method designed to improve curcumin's bioavailability. We performed a single-center crossover experiment to compare the new product with standard 95% curcumin in the blood plasma of twelve healthy adults (10 males, 2 females). Total bioavailability of curcumin and its sulfate and glucuronide conjugates from the test product, measured by their areas under the curve over 12 h (AUC0-T ), showed a combined increase of 178-fold over standard curcumin and its conjugates from the reference product. The new product represents a significant improvement for providing greater bioavailability of curcumin, as compared with several other branded preparations. It therefore has broad applications for preparing curcumin as a more effective health ingredient in functional foods, beverages, and nutraceuticals.